Incorporating SGLT2 Inhibitors into Breast Cancer Management: Cardioprotection During Anthracycline Therapy - Azam, Abdullah; Abdulaziz, Fatima; Asim , Mohammad (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Sodium-glucose co-transporter 2 (SGLT2) inhibition was first explored 130 years ago by Belgian and French scientists. Currently, four oral SGLT2 inhibitors have been approved by the U.S. Food and Drug Administration and the European Medicines Agency: canagliflozin, dapagliflozin, empagliflozin, and ertugliflozin. SGLT2 inhibitors block glucose reabsorption in the proximal tubules and lead to glucosuria. (1) The cardioprotective and renoprotective effects of SGLT2 inhibitors in patients with type 2 diabetes mellitus are well established. They have been shown to reduce cardiovascular mortality and heart failure-related hospitalisations while also slowing the progression of renal disease and stabilizing the estimated glomerular filtration rate. (2) A meta-analysis published in 2024 examined the cardioprotective role of SGLT2 inhibitors for anthracycline-induced cardiotoxicity. It combined data from three cohort studies, totaling 2817 patients. The study's results demonstrated a significant reduction in overall mortality (p = 0.005) and heart failure (HF) hospitalizations (p = 0.05). (3) Additionally, a retrospective cohort study investigated diabetic cancer patients receiving anthracyclines, comparing those who were on SGLT2 inhibitors during receiving SGLT2 inhibitors and those not. The study found a significantly lower incidence of cardiac events (heart failure incidence, HF admissions, new-onset cardiomyopathy (Greater-Than 10% decline in ejection fraction to Less-Than 53%), and clinically significant arrhythmias) in the SGLT2 inhibitor group (p = 0.025). (4) A 2022 study reported a five-year prevalence of 321,265 cancer cases in Pakistan and highlighted that Pakistan has the highest breast cancer prevalence in the region. (5) Anthracyclines, a class of chemotherapeutic agents, are known for their efficacy against solid tumors like breast cancer. However, their use is limited by significant cardiotoxic effects, including cardiac dysfunction. (3) (4) Given their cardioprotective properties, the authors suggest adding SGLT2 inhibitors to the treatment plan of breast cancer patients receiving anthracyclines. This may reduce these adverse effects and improve overall treatment outcomes.